Penilaian Sertifikat Penerapan Penanganan yang Baik Psat (Sppb-Psat) Produk Buah Kering di UMKM Vakuola, Yogyakarta - Rozikin , Faiz; Fitri , Ichlasia Ainul; Yulianto, Wisnu Adi (Universitas Mercu Buana Yogyakarta, 2026)
Indonesia has an abundant supply of tropical fruits, but they are highly perishable. One way to extend their shelf life and preserve their nutritional quality is through the drying process to produce dried fruit. However, processing at the SME level is highly susceptible to contamination that affects food safety. Based on Ministry of Agriculture Regulation No. 15 of 2021, food handling units are required to meet the standards of the Certificate of Good Handling Practices for Fresh Plant-Based Foods (SPPB-PSAT) to ensure product quality. This study aims to assess the basic feasibility of dried fruit processing at the Vakuola SME in Yogyakarta using the SPPB-PSAT framework. Additionally, the study aims to validate observational findings through laboratory testing, including microbiological tests (ALT) and chemical analyses (moisture content, ash content, reducing sugars, and vitamin C). The study was conducted at the Vakuola UMKM and the Mercu Buana University Laboratory in Yogyakarta from October to December 2023. The samples used were dried lemons, red apples, and strawberries. SPPB-PSAT assessment data were collected through observations of location, buildings, sanitation facilities, and documentation. Based on laboratory test results, the lemon product had a Total Plate Count (TPC) of 4 × 10⁵ colonies/g, followed by apples at 1 × 10⁵ colonies/g, and strawberries at 3.5 × 10³ colonies/g. In proximate analysis, the moisture content of the products ranged from 19.01% to 23.46%, with the highest vitamin C content found in dried strawberries (6.15%) and the highest reducing sugar content in dried apples (41.98%). The implementation of basic hygiene standards at the Vakuola SME still requires significant improvement, particularly regarding storage facilities equipped with temperature/humidity controls and the enforcement of proper use of specialized work attire to prevent cross-contamination.